KEBIJAKAN PENGEMBANGAN KURIKULUM PENDIDIKAN ISLAM (Studi Histori dan Regulasi di Indonesia) - Selamet; Supiana; Qiqi Yuliati Zaqiah (Program Studi Manajemen Pendidikan Islam, 2023)
Curriculum is the most important component in education. Curriculum development in Islamic education is a necessity, because changes must occur following the times. So the purpose of this writing is to examine policies related to Islamic education curriculum development, especially in Indonesia with due regard to history and applicable regulations. This paper uses the library research method with a content analysis approach. The results of the study show that the Islamic education curriculum in historical review from the time of independence to the reform era continues to change according to conditions and needs. The development of the Islamic education curriculum is divided into 3 periods; namely first, during the old order, there were 3 changes, namely the 1947, 1952, and 1964 curricula; secondly, during the New Order era, there were 4 changes, namely the 1968, 1975, 1984, and 1994 curricula; third, the reformation period, there were 3 changes, namely the 2004 curriculum (KBK), 2006 curriculum (KTSP), the 2013 curriculum which has been used until now. Whereas in the review of Islamic education curriculum regulations there are 4 categories namely: first, madrasah curriculum regulations follow Law number 20 of 2003 concerning the national education system; second, the pesantren curriculum regulations follow Law number 18 of 2019 concerning Islamic Boarding Schools; third, the curriculum regulations for Islamic religious tertiary institutions are based on Law number 12 of 2012 concerning higher education; and fourth, regulation of the Islamic religious education curriculum for public schools/campuses based on Law number 20 of 2003